Quality Improvement of Compost from Empty Oil Palm Fruit Bunch by the Addition of Boiler Ash and its effect on Chemical Properties of Ultisols and the Production of Mustard (Brassica juncea L.) - Sri Mulyani; Dyah Tjahyandari Suryaningtyas; . Suwardi; . Suwarno (UNIVERSITY OF LAMPUNG, 2016)
Productions of crude palm oil (CPO) produce waste which include the empty oil palm fruit bunch (EOPFB), palm oil mill effluent, shells, and fiber. The combustions of shell and fiber as boiler feed produce waste in the form of boiler ash. Boiler ash is very potential to use as an additive to improve quality of the EOPFB compost. The objectives of this research were to study : 1) effect of boiler ash on the quality of the EOPFB compost, 2) effect of EOPFB compost on the chemical properties of Ultisol, and the yield of mustard. The first experiment was about quality improvement of compost from EOPFB by the addition of boiler ash. The treatments applied were four dose levels of boiler ash: K1= 0%, K2 = 15%, K3 = 25%, and K4 = 35%. The second experiment was greenhouse pot experiment. This experiment was consisted of thirteen treatments with three replications arranged in completely randomized design (CRD). The treatments applied were: four types of compost from the first experimental results aplied to the soil with four dose levels, i.e : 0, 10, 20 and 30 Mg ha-1. The results showed that the addition of boiler ash at the beginning of the composting process improved the quality of the EOPFB compost: which increased pH, amount of humic acids, macro and micro nutrients content and decreased content of Pb. The aplication of all compost –K1, K2, K3, K4– to Ultisol increased pH H2O, P2O5, organic-C, total-N, exchangeable-Ca, exchangeable-K and yield of mustard and decreased exchangeable-H, exchangeable-Al. Moreover the yield of mustard was increased about 84% (33.9 g plant-1) with K4 at doses 20 Mg ha-1 and 85% (34.1 g plant-1) with K3 at doses 10 Mg ha-1.